Eye-hand synchronisation in xylophone performance: Two case-studies with african and western percussionists - Fabrice Marandola (Bern Open Publishing, 2019)
This article is the result of a first foray into xylophone performance with percussionists from Canada and Cameroon. It proposes to use the combination of Eye-Stroke Span (ESS), Fix- ation-Duration and Note-Pattern indexes to analyze free-score and performance oriented musical tasks, instead of eye-hand span or awareness span for sight-reading and score-based eye-tracking research in music. Based on measurements realized with a head-mounted eye- tracker system, the research examines gaze-movements related to eye-hand synchronization in xylophone performance with musicians coming from three different ethnic groups from Cameroon (Bedzan Pygmies, Tikar and Eton) and classically trained Western percussionists (Canada). Increases in tempo are found to involve a diminution of the number of fixations, but not proportionally, as well as changes in lateral gaze shifts. Fixation-Duration and Note- Pattern are closely related but not identical, while ESS is relatively more independent. These gaze patterns are consistent within individuals, but not across individuals. Cameroonian mu- sicians tend to look away from their instrument, interacting with their peers or with the au- dience. When they look at their keyboard, preliminary measures of ESS were found similar to the ESS of Western performers.